Syringocystadenoma papilliferum developed on sebaceous nevus. Three pediatric cases. - Guareschi, E.; Di Lernia, V. (European Journal of Pediatric Dermatology, 2009)
Sebaceous nevus is a congenital organoid nevus. It is mainly located on the scalp and appears as a hairless yellowish plaque at birth or soon after. Sebaceous nevus changes with growth being sebaceous glands responsive to hormones at puberty. Since benign and malignant tumors can arise within sebaceous nevus, short follow-up and surgical excision are probably the better medical behavior to manage these lesions when changes appear. Here are reported three pediatric cases of syringocystadenoma papilliferum developed in the context of sebaceous nevus.